A systematic review on effectiveness of sensory integration intervention in reducing self-injurious behavior among children with Autism/ Fatin Nur Afiqah Zulkifli, Masne Kadar, Akehsan Dahlan - Zulkifli, Fatin Nur Afiqah; Kadar, Masne; Dahlan, Akehsan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Children with Autism spectrum disorder (ASD are common to have a self-injurious behavior compared to the other neurodevelopmental disabilities. These behaviors may cause the child to engages in a behavior that cause physical harms such as head banging or self-biting. Previous reviews examined the effects of sensory integration interventions comparing with other intervention such as behavior intervention. This systematic review examined the research evidence from 2009 to 2018. A total of 4 studies were reviewed: 2 examined the effects of sensory integration therapy compared to behavior intervention and other 2 are the effect of using sensory integration. Only 1 positive effects were found in reducing self-injurious behavior meanwhile the other three studies may show lack of evidence due to the limitation of the study itself such as use of single clinical site and small sample size.